Improving solitary play with a typically developing preschooler. (1st March 2018) - Beaulieu, Lauren; Povinelli, Jaime L.
Abstract : We evaluated the effects of delivering specific instructions (e.g., "Here are some puzzles. Complete two of them while I read.") on solitary play with a typically developing 3‐year‐old. We gradually increased the response requirements described in the specific instruction and found that specific instructions improved the number of solitary play responses and the duration of engagement. During a treatment extension, improvements in solitary play were observed with the classroom teacher and a novel toy. The father, teacher, and preschool director found the treatment to be highly effective and acceptable.